2016
DOI: 10.1002/mnfr.201500804
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of the bitter taste receptor TAS2R38 are associated with obesity and impact on single immune traits

Abstract: Scope: Changes in genetic variations affecting the taste receptor, type 2, member 38 (TAS2R38) may identify the interacting mechanism leading to obesity and potential associations with proteins partaking in innate immunity, such as surfactant protein D (SPD) and mannanbinding lectin (MBL). Methods and results:We evaluated haplotypes of the bitter-taste receptor TAS2R38 in an identification sample of 210 women in different weight conditions, including anorexia nervosa and obesity. The association with SPD and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 54 publications
4
33
1
Order By: Relevance
“…Two papers (Fernandez‐Aranda et al, 2016; Ortega et al, 2016) were confirmed through correspondence with the authors to have reported on overlapping samples, with some of the cases and controls taking part in both studies. As this review did not incorporate a meta‐analysis, both studies were retained in the review, with the limitations and implications of their overlapping sample highlighted in the results and the discussion.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Two papers (Fernandez‐Aranda et al, 2016; Ortega et al, 2016) were confirmed through correspondence with the authors to have reported on overlapping samples, with some of the cases and controls taking part in both studies. As this review did not incorporate a meta‐analysis, both studies were retained in the review, with the limitations and implications of their overlapping sample highlighted in the results and the discussion.…”
Section: Resultsmentioning
confidence: 75%
“…Additionally, unlike many of the studies in this review, Fernández‐Aranda et al controlled for a number of potential variables in their study design, including smoking and medication use. Nonetheless, that a subsequent study using a similar design and an overlapping sample found no significant differences highlights the difficulty in replicating these findings (Ortega et al, 2016). …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations